Between Doctrine and Custom: A Sociological Study on the Distribution of Zakat to Santri - Musanna, Khadijatul; Fitri, Aulia; Junaidi; Azhar; Badruzaman, Akhmad Roja (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
This research evaluates the practice of zakat distribution to santri in Aceh through the sociology of Islamic law approach. In Acehnese society, religious figures such as Dayah, Teungku, and Abi have high authority that influences socio-religious practices, including the allocation of zakat. This respect forms a social doctrine that prioritizes santri as zakat recipients, even though their economic status is not always categorized as fakir (destitute) or miskin (poor) in the classical zakat provisions. This research uses qualitative methods, in-depth interview techniques, and participatory observation involving Tgk Imum, amil, and Dayah leaders in ten villages. The results identified three main factors shaping zakat distribution: community perceptions of santri, the strength of social networks, and the role of ʿurf (local custom). Santri are positioned as fighters in the cause of Allah (fī sabīlillāh), and their proximity to religious authorities strengthens this legitimacy. Based on sahih ʿurf, this practice integrates sharia principles with local socio-cultural dynamics.